Preparation method of iron nanoparticle loaded nitrogen-doped biochar catalyst and application of iron nanoparticle loaded nitrogen-doped biochar catalyst in degradation of organic pollutants in activated persulfate system

CN122974353APending Publication Date: 2026-10-27HEILONGJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611430611.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-15
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

在众多催化活化方法中,热、紫外光、超声等方法能量成本高;铁基催化剂Fe3+向Fe2+的还原速率极慢,导致催化剂迅速失活,且易产生铁泥沉淀;传统碳材料活化过硫酸盐主要依赖缺陷位点或表面官能团,活性位点单一,效果有限

Benefits of technology

[0014](1)本发明以经济绿色的方法合成一种高效铁纳米颗粒负载掺氮生物炭催化剂。同时使用铁纳米颗粒负载掺氮生物炭催化剂和光催化的双催化活化过硫酸盐高效降解有机污染物。铁纳米颗粒与掺氮生物炭构成“双活性位点”协同催化,光催化则通过光生电子进一步促进铁循环并增强自由基生成,最终通过自由基路径与非自由基路径共同高效降解有机污染物。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122974353A_ABST
    Figure CN122974353A_ABST
Patent Text Reader

Abstract

The application relates to a preparation method of an iron nanoparticle loaded nitrogen-doped biochar catalyst and application of the iron nanoparticle loaded nitrogen-doped biochar catalyst in degradation of organic pollutants in an activated persulfate system, and relates to the technical field of environmental functional materials. Method: biochar and potassium ferrate are added into distilled water, and then dried after magnetic stirring; then, the biochar and the potassium ferrate are placed in a porcelain boat of a vacuum tube furnace, heated to 750-900 DEG C and kept for 0.5-1.5 h; after the keeping, the biochar and the potassium ferrate are cooled to room temperature by using inert gas, and then subjected to etching, cleaning and freeze drying to obtain an iron nanoparticle loaded nitrogen-doped biochar catalyst. The application of the iron nanoparticle loaded nitrogen-doped biochar catalyst in degradation of organic pollutants in an activated persulfate is used for degrading naphthalene, phenanthrene and benzo[a]pyrene. The application can obtain a preparation method of an iron nanoparticle loaded nitrogen-doped biochar catalyst and application of the catalyst in degradation of organic pollutants in an activated persulfate system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of environmental functional materials technology, specifically to a method for preparing a nitrogen-doped biochar catalyst supported on iron nanoparticles and its application in the degradation of organic pollutants in an activated persulfate system. Background Technology

[0002] Persulfate (PDS, S2O8) 2- The redox potential of sulfoxide is approximately 2.01 V, comparable to that of ozone, but its O2O bond energy is as high as 140 kJ / mol, making it difficult to spontaneously break at room temperature to attack organic pollutants. Therefore, traditional processes must rely on heat, alkali, ultraviolet light, ultrasound, transition metals, or carbon materials to input energy or electrons, forcing the O2O bonds to break and generating sulfate radicals (sulfate free radicals). Active species such as Fe. Among numerous catalytic activation methods, methods such as heat, ultraviolet light, and ultrasound have high energy costs; iron-based catalysts Fe 3+ To Fe 2+ The reduction rate is extremely slow, which leads to rapid deactivation of the catalyst and easy precipitation of iron sludge. Traditional carbon materials mainly rely on defect sites or surface functional groups to activate persulfate, resulting in a single active site and limited effectiveness.

[0003] Traditional persulfate systems have limited effectiveness in degrading organic pollutants and struggle to maintain sustained activity. Among numerous catalytic activation methods, catalysts supported on iron nanoparticles can efficiently degrade persulfates, but the synthesis of traditional iron nanoparticle-supported catalysts is complex, and their activation and degradation effects are difficult to stabilize. Summary of the Invention

[0004] The purpose of this invention is to solve the above-mentioned technical problems by providing a method for preparing a nitrogen-doped biochar catalyst supported on iron nanoparticles and its application in the degradation of organic pollutants in an activated persulfate system.

[0005] A method for preparing a nitrogen-doped biochar catalyst supported on iron nanoparticles, comprising the following steps:

[0006] Step S1:

[0007] After washing and air-drying, the biomass is pulverized and sieved to obtain biomass powder. The biomass powder and urea are added to distilled water, magnetically stirred, and then dried. The mixture is then placed in a ceramic boat in a vacuum tube furnace and heated to 500-700℃, and kept at 500-700℃ for 0.5-1.5 hours. After the holding time, the mixture is cooled to room temperature using an inert gas to obtain biochar.

[0008] Step S2:

[0009] The biochar and K2FeO4 obtained in step S1 were added to distilled water, magnetically stirred and dried, and then placed in a ceramic boat in a vacuum tube furnace and heated to 750~900℃. The temperature was maintained at 750~900℃ for 0.5~1.5h. After the temperature maintenance, the mixture was cooled to room temperature with an inert gas, and then etched, cleaned and freeze-dried to obtain a nitrogen-doped biochar catalyst supported on iron nanoparticles.

[0010] An application of an iron nanoparticle-supported nitrogen-doped biochar catalyst, wherein the iron nanoparticle-supported nitrogen-doped biochar catalyst is used in the degradation of organic pollutants in an activated persulfate system, wherein the organic pollutants are naphthalene, phenanthrene and benzo[a]pyrene.

[0011] The principle of this invention:

[0012] Compared to traditional processes, the "iron nanoparticle-supported nitrogen-doped biochar + photocatalysis" dual-catalytic system of this invention achieves a triple breakthrough in addressing the bottlenecks of traditional processes: the activation load is shared by nitrogen-doped carbon sites, preventing iron sites from solely undertaking the entire persulfate activation task; photogenerated electrons accelerate the Fe(III) / Fe(II) cycle, breaking the rate-limiting step of iron-based catalysis; and a mixed mechanism of coexistence of free radicals and non-free radicals enhances adaptability to complex water bodies while maintaining the degradation rate. Traditional processes represent a "single-point breakthrough," while this invention represents a "system synergy."

[0013] The beneficial effects of this invention are:

[0014] (1) This invention synthesizes a highly efficient iron nanoparticle-supported nitrogen-doped biochar catalyst using an economical and green method. Simultaneously, the iron nanoparticle-supported nitrogen-doped biochar catalyst and photocatalysis are used for dual-catalytic activation of persulfate to efficiently degrade organic pollutants. The iron nanoparticles and nitrogen-doped biochar form a "dual active site" for synergistic catalysis, while photocatalysis further promotes iron cycling and enhances free radical generation through photogenerated electrons. Ultimately, organic pollutants are efficiently degraded through both free radical and non-free radical pathways.

[0015] (2) The present invention synthesizes nitrogen-doped biochar catalyst supported on iron nanoparticles using a green and economical method.

[0016] (3) In this invention, iron nanoparticles supported on nitrogen-doped biochar catalyst and photocatalytic dual catalytic system activate persulfate to efficiently degrade organic pollutants.

[0017] (4) This invention achieves the dual goal of “treating pollution with waste”.

[0018] This invention provides a method for preparing a nitrogen-doped biochar catalyst supported on iron nanoparticles and its application in the degradation of organic pollutants in an activated persulfate system. Attached Figure Description

[0019] Figure 1 This image shows a transmission electron microscope (TEM) image of the nitrogen-doped biochar catalyst supported on iron nanoparticles prepared in Example 1.

[0020] Figure 2 X-ray diffraction (XRD) pattern of the nitrogen-doped biochar catalyst supported on iron nanoparticles prepared in Example 1.

[0021] Figure 3 The graph shows the degradation data of pollutants in the dual-catalytic activation persulfate system based on the nitrogen-doped biochar catalyst supported on iron nanoparticles prepared in Example 1.

[0022] Figure 4 The graph shows the reusability data of the iron nanoparticle-supported nitrogen-doped biochar catalyst prepared in Example 1 in the dual-catalytic system for degrading phenanthrene. Detailed Implementation

[0023] Specific Implementation Method 1: This implementation method describes a method for preparing a nitrogen-doped biochar catalyst supported on iron nanoparticles, which is carried out according to the following steps:

[0024] Step S1:

[0025] After washing and air-drying, the biomass is pulverized and sieved to obtain biomass powder. The biomass powder and urea are added to distilled water, magnetically stirred, and then dried. The mixture is then placed in a ceramic boat in a vacuum tube furnace and heated to 500-700℃, and kept at 500-700℃ for 0.5-1.5 hours. After the holding time, the mixture is cooled to room temperature using an inert gas to obtain biochar.

[0026] Step S2:

[0027] The biochar and K2FeO4 obtained in step S1 were added to distilled water, magnetically stirred and dried, and then placed in a ceramic boat in a vacuum tube furnace and heated to 750~900℃. The temperature was maintained at 750~900℃ for 0.5~1.5h. After the temperature maintenance, the mixture was cooled to room temperature with an inert gas, and then etched, cleaned and freeze-dried to obtain a nitrogen-doped biochar catalyst supported on iron nanoparticles.

[0028] Specific Implementation Method Two: The difference between this implementation method and Specific Implementation Method One is that the biomass mentioned in step S1 is beet stems and leaves.

[0029] The other steps are the same as in Specific Implementation Method 1.

[0030] Specific Implementation Method 3: The difference between this implementation method and Specific Implementation Method 1 or 2 is that: in step S1, distilled water is used to wash the biomass 3 to 5 times.

[0031] The other steps are the same as in Specific Implementation Method 1 or 2.

[0032] Specific Implementation Method Four: The difference between this implementation method and Specific Implementation Methods One to Three is that in step S1, the powder is passed through a 60-mesh sieve.

[0033] The other steps are the same as those in Specific Implementation Methods One to Three.

[0034] Specific Implementation Method 5: The difference between this implementation method and Specific Implementation Methods 1 to 4 is that the ratio of the mass of biomass powder, the mass of urea and the volume of distilled water in step S1 is (1.5~3.5) g : (0.2~0.5) g : (50~150) mL.

[0035] The other steps are the same as those in Specific Implementation Methods One through Four.

[0036] Specific Implementation Method Six: The difference between this implementation method and Specific Implementation Methods One to Five is that the heating rate in both step S1 and step S2 is 5~10℃ / min.

[0037] The other steps are the same as those in Specific Implementation Methods 1 to 5.

[0038] Specific Implementation Method Seven: The difference between this implementation method and Specific Implementation Methods One to Six is ​​that in both steps S1 and S2, the magnetic stirring is performed at a speed of 250~450r / min for 20~24h, and after magnetic stirring, the magnetic stirring is performed in a constant temperature drying oven at 50~80℃.

[0039] The other steps are the same as those in Specific Implementation Methods 1 to 6.

[0040] Specific Implementation Method Eight: The difference between this implementation method and Specific Implementation Methods One to Seven is that the ratio of the mass of biochar, the mass of K2FeO4 and the volume of distilled water in step S2 is (1.5~2.5) g : (0.9~1.1) g : (50~150) mL.

[0041] The other steps are the same as those in Specific Implementation Methods 1 to 7.

[0042] Specific Implementation Method Nine: The difference between this implementation method and Specific Implementation Methods One to Eight is that the inert gas mentioned in step S2 is nitrogen; in step S2, acid is used for etching, deionized water is used for cleaning until neutral, and the mixture is placed in a freeze dryer for freeze drying.

[0043] The other steps are the same as those in Specific Implementation Methods 1 to 8.

[0044] Specific Implementation Method 10: This implementation method describes the application of an iron nanoparticle-supported nitrogen-doped biochar catalyst in the degradation of organic pollutants in an activated persulfate system. The organic pollutants are naphthalene, phenanthrene, and benzo[a]pyrene.

[0045] The beneficial effects of the present invention are verified using the following embodiments:

[0046] Example 1: A method for preparing a nitrogen-doped biochar catalyst supported on iron nanoparticles, comprising the following steps:

[0047] Step S1:

[0048] The beet stems and leaves were washed three times with distilled water and then air-dried naturally. The air-dried beet stems and leaves were then pulverized into powder using a grinder, passed through a 60-mesh sieve, and stored for later use. 2g of beet stem and leaf powder and 0.3g of urea were poured into a 250mL beaker containing 100mL of distilled water and placed on a magnetic stirring table. The mixture was magnetically stirred at 400r / min for 24h. After that, it was dried in a constant temperature drying oven at 60℃. Then, it was placed in a porcelain boat in a vacuum tube furnace and heated to 600℃ at a heating rate of 10℃ / min. The temperature was then maintained at 600℃ for 1h. After the holding time, it was cooled to room temperature using continuous nitrogen gas to obtain biochar (NBC), which was stored in a sealed bag for later use.

[0049] Step S2:

[0050] 2g of biochar and 0.99g of K2FeO4 were mixed and poured into a 250mL beaker containing 100mL of distilled water. The mixture was placed on a magnetic stirring table and magnetically stirred at 400r / min for 24h. After drying in a constant temperature drying oven at 60℃, the mixture was placed in a porcelain boat in a vacuum tube furnace and heated to 800℃ at a heating rate of 10℃ / min. The temperature was then maintained at 800℃ for 1h. After the holding time, the mixture was cooled to room temperature using continuous nitrogen gas. The material was then removed and slightly etched with acid to remove exposed unstable iron species. After washing with deionized water until neutral, the mixture was freeze-dried in a freeze dryer to obtain a nitrogen-doped biochar catalyst supported on iron nanoparticles.

[0051] Experiment content:

[0052] The experiment was conducted in a 50 mL Erlenmeyer flask under 300 W xenon lamp irradiation. The reaction system volume was 10 mL, and the initial concentration of the contaminant was set to 1 mg / L. The mixture was shaken in a constant temperature water bath at 200 rpm. The amount of nitrogen-doped biochar catalyst supported on the iron nanoparticles was 0.4 g / L, and the amount of persulfate (PS) was 0.3 g / L. After 90 min of reaction, excess 1 mol / L Na₂S₂O₃ (reaction terminator) was added to terminate the reaction. A mixture of acetone and n-hexane at a volume ratio of 1:1 was used as the extraction solvent. The supernatant was collected as the sample to be tested and stored for analysis on a high-performance liquid chromatograph (HPLC, Agilent 1260, USA).

[0053] Figure 1 This image shows a transmission electron microscope (TEM) image of the nitrogen-doped biochar catalyst supported on iron nanoparticles prepared in Example 1. Figure 2 The image shows the X-ray diffraction (XRD) pattern of the nitrogen-doped biochar catalyst supported on iron nanoparticles prepared in Example 1. Figure 1 As shown, the lattice spacing is 0.210 nm, corresponding to the (211) crystal plane of Fe3C, and at the same time Figure 2 The XRD results also showed that the peak at 42.8° represented the (211) crystal plane of Fe3C, indicating that the iron nanoparticles were successfully loaded onto biochar. Figure 2 The appearance of Fe 0 The characteristic peaks, located at 44.6°, 65.0°, and 82.3°, represent Fe. 0 The (110), (200), and (211) crystal planes are observed. The peak at 26.4° is attributed to the (002) crystal plane of graphitic carbon, the characteristic peak at 51.5° is considered to be FeOOH, and the characteristic peak at 43.6° is considered to be the (011) crystal plane of Fe3N. Combining the results of TEM and XRD, it is speculated that the nitrogen-doped biochar supported on iron nanoparticles exhibits a core-shell structure, with Fe as the structural center. 0 The outer shell consists of oxides such as Fe3C and FeOOH. The short C-Fe bonds reduce the resistance and shorten the distance for electron transfer from organic pollutant molecules to the electron-rich Fe center. Fe(III) can accept electrons to regenerate Fe(II), thereby maintaining a highly efficient and continuous activation capacity. At the same time, this coating state can, to some extent, prevent Fe from being absorbed. 0 The oxidation of iron nanoparticles on nitrogen-doped biochar has a higher specific surface area and smaller iron particle size. The high specific surface area gives the material more active sites, which is beneficial for adsorption and degradation. The smaller iron particle size makes it easier to activate persulfate through electron transfer via valence state change.

[0054] Figure 3 This graph shows the degradation data of pollutants in a persulfate system based on the dual-catalytic activation of the nitrogen-doped biochar catalyst supported on iron nanoparticles prepared in Example 1; as shown. Figure 3 As shown, iron nanoparticles supported on nitrogen-doped biochar catalysts were used for the dual-catalytic activation of persulfate to degrade naphthalene (NAP), phenanthrene (PHE), and benzo[a]pyrene (BaP) in polycyclic aromatic hydrocarbons. After 90 min, the degradation rates were 95.8%, 94.0%, and 87.3%, respectively, demonstrating that the dual-catalytic system can efficiently degrade naphthalene, phenanthrene, and benzo[a]pyrene using persulfate in a short time. Based on the high degradation efficiency observed in the laboratory, the system was tested under natural light. The results showed that the degradation rates of NAP, PHE, and BaP under natural light were 90.1%, 89.5%, and 86.4% of the laboratory degradation rates, respectively. Although the degradation rates decreased, the system still showed good degradation performance for polycyclic aromatic hydrocarbons.

[0055] In the dual-catalytic system, the change in iron valence state and nitrogen configuration of nitrogen-doped biochar supported on iron nanoparticles effectively activates persulfate to generate active substances. Simultaneously, photocatalysis promotes electron transfer from the nano-iron loaded on the nitrogen-doped biochar, leading to the transfer of electrons to persulfate ions on the biochar surface and the generation of active substances, thus achieving highly efficient degradation of pollutants. The core-shell structure plays a crucial role in this system. Fe 0 The core generates electrons under visible light excitation, which are then directionally transferred to the biochar surface via the Fe3C(211) crystal plane; simultaneously, the FeOOH shell participates in the Fe... 2+ / Fe 3+ Valence state cycling maintains the regeneration of active sites, while the dense shell effectively blocks dissolved oxygen from affecting Fe. 0 The passivation ensures a continuous supply of electrons. Therefore, electrons activate persulfate (PDS) via two pathways: first, electrons enriched in biochar directly attack the O / O bonds of PDS, generating... Secondly, photogenerated electrons reduce dissolved oxygen to produce... This leads to the generation of disproportionation. 1 O2. In addition... It reacts with H₂O to form ·OH. Active species. , , , 1 O2 works synergistically to attack polycyclic aromatic hydrocarbons, ultimately degrading them into CO2 and H2O.

[0056] In the toxicity test of water samples before and after degradation, the mortality rate of large fleas reached 91.1% in the 48-hour acute toxicity test before degradation, while the mortality rate in the water sample after degradation was 9.8%, indicating a significant decrease in toxicity.

[0057] Figure 4 The graph shows the reusability data of the iron nanoparticle-supported nitrogen-doped biochar catalyst prepared in Example 1 in the dual-catalytic system for dephenerene degradation; as shown. Figure 4As shown, the nitrogen-doped biochar catalyst supported on iron nanoparticles still achieved a degradation rate of 83.4% in the fifth cycle, indicating that the dual-catalytic system can still ensure efficient degradation of phenanthrene after multiple uses.

Claims

1. A method for preparing a nitrogen-doped biochar catalyst supported on iron nanoparticles, characterized in that, The preparation method is carried out according to the following steps: Step S1: After washing and air-drying, the biomass is pulverized and sieved to obtain biomass powder. The biomass powder and urea are added to distilled water, magnetically stirred, and then dried. The mixture is then placed in a ceramic boat in a vacuum tube furnace and heated to 500-700℃, and kept at 500-700℃ for 0.5-1.5 hours. After the holding time, the mixture is cooled to room temperature using an inert gas to obtain biochar. Step S2: The biochar and K2FeO4 obtained in step S1 were added to distilled water, magnetically stirred and dried, and then placed in a ceramic boat in a vacuum tube furnace and heated to 750~900℃. The temperature was maintained at 750~900℃ for 0.5~1.5h. After the temperature maintenance, the mixture was cooled to room temperature with an inert gas, and then etched, cleaned and freeze-dried to obtain a nitrogen-doped biochar catalyst supported on iron nanoparticles.

2. The method for preparing a nitrogen-doped biochar catalyst supported on iron nanoparticles according to claim 1, characterized in that, The biomass mentioned in step S1 is beet stems and leaves.

3. The method for preparing a nitrogen-doped biochar catalyst supported on iron nanoparticles according to claim 1, characterized in that, In step S1, the biomass is washed 3 to 5 times with distilled water.

4. The method for preparing a nitrogen-doped biochar catalyst supported on iron nanoparticles according to claim 1, characterized in that, After crushing in step S1, the powder is passed through a 60-mesh sieve.

5. The method for preparing a nitrogen-doped biochar catalyst supported on iron nanoparticles according to claim 1, characterized in that, The ratio of the mass of biomass powder, the mass of urea, and the volume of distilled water in step S1 is (1.5~3.5) g : (0.2~0.5) g : (50~150) mL.

6. The method for preparing a nitrogen-doped biochar catalyst supported on iron nanoparticles according to claim 1, characterized in that, The heating rate in both steps S1 and S2 is 5~10℃ / min.

7. The method for preparing a nitrogen-doped biochar catalyst supported on iron nanoparticles according to claim 1, characterized in that, In both steps S1 and S2, the magnetic stirring is performed at a speed of 250~450 r / min for 20~24 h. After magnetic stirring, the mixture is dried in a constant temperature drying oven at 50~80℃.

8. The method for preparing a nitrogen-doped biochar catalyst supported on iron nanoparticles according to claim 1, characterized in that, The ratio of the mass of biochar, the mass of K2FeO4 and the volume of distilled water in step S2 is (1.5~2.5) g : (0.9~1.1) g : (50~150) mL.

9. The method for preparing a nitrogen-doped biochar catalyst supported on iron nanoparticles according to claim 1, characterized in that, The inert gas mentioned in step S2 is nitrogen; in step S2, acid is used for etching, deionized water is used to clean until neutral, and the mixture is placed in a freeze dryer for freeze drying.

10. The application of an iron nanoparticle-supported nitrogen-doped biochar catalyst prepared by the method according to any one of claims 1-9, characterized in that, The application of the iron nanoparticle-supported nitrogen-doped biochar catalyst in the degradation of organic pollutants in an activated persulfate system, wherein the organic pollutants are naphthalene, phenanthrene, and benzo[a]pyrene.